Forces of nature : new perspectives on Korean environments - Fedman, David; Kim, Eleana Jean, 1971-; Park, Albert L.; Sherif, Ann (The environments of East Asia, 2023)
"Brings together scholars at the forefront of the emerging field of Korean environmental humanities to offer a multidisciplinary and transhistorical account of the Korean peninsula that centers the dynamic entanglements of human and nonhuman forces--flora, fauna, mineral deposits, and climatic conditions"--